2014
DOI: 10.1002/2013tc003502
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the geometry of the active Shanchiao Fault in the Taipei metropolis, northern Taiwan, and the reactivation relationship with preexisting orogen structures

Abstract: The Shanchiao Fault is an active normal fault with documented paleoearthquakes in the Taipei metropolis, Taiwan. While posing direct seismic threat on the multimillion population, its crustal-scale fault plane configuration has not been constrained. This study presents the first attempt to resolve the fault plane dip changes of the Shanchiao Fault within the upper crust by forward modeling late Quaternary deformation. Tectonic subsidence over the last~23 ka is estimated from vertical displacements of a rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 80 publications
(148 reference statements)
0
9
0
Order By: Relevance
“…Accordingly, the deformation front of the Taiwan orogenic wedge roughly separates the foreland basin to the west from the mountain belt to the east in the terrestrial domain (thick black dash line in Figure 1) [11,20], and it separates the less deformed East China Sea continental shelf to the west from the deformed, collapsed Taiwan orogenic wedge to the east in offshore Northern Taiwan (thick blue dash line in Figure 1) [12]. West of the Taipei Basin, the deformation front seems to run approximately along the Shanchiao Fault [23], an active normal fault with documented paleoearthquakes in the Taipei metropolis [24]. Along the northward extension of the Shanchiao Fault, the deformation front runs seemingly along the Chinshan Fault, which has an at-least 7 km extension observed in the underwater domain [25].…”
Section: Geological Setting 21 Regional Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the deformation front of the Taiwan orogenic wedge roughly separates the foreland basin to the west from the mountain belt to the east in the terrestrial domain (thick black dash line in Figure 1) [11,20], and it separates the less deformed East China Sea continental shelf to the west from the deformed, collapsed Taiwan orogenic wedge to the east in offshore Northern Taiwan (thick blue dash line in Figure 1) [12]. West of the Taipei Basin, the deformation front seems to run approximately along the Shanchiao Fault [23], an active normal fault with documented paleoearthquakes in the Taipei metropolis [24]. Along the northward extension of the Shanchiao Fault, the deformation front runs seemingly along the Chinshan Fault, which has an at-least 7 km extension observed in the underwater domain [25].…”
Section: Geological Setting 21 Regional Structurementioning
confidence: 99%
“…Though there are only three volcanic islets, we should note that volcanism also occurs underwater and may not be visible above sea level. In fact, recent observations have shown some subsurface volcanic features [12] and seafloor edifices [23]. Therefore, the number of volcanoes and the volcanic activity offshore from Northern Taiwan are very likely to have been underestimated.…”
Section: Northern Taiwan Volcanic Zone (Ntvz)mentioning
confidence: 99%
“…The TVG is cut in the middle by the Shanchiao fault ( Fig. 1b), an eastward-dipping, listric normal fault 1 . Early studies indicated that the TVG had been active during 2.8-0.1 Ma 2-4 , but has stayed dormant ever since 5 .…”
Section: Dense Seismic Arrays Deny a Massive Magma Chamber Beneath Thmentioning
confidence: 99%
“…The collision was achieved in two stages: first the Manila Trench was choked by the arrival of Chinese continental margin after subduction of the South China Sea (Lin et al 2009); then shortening within the upper Philippines Sea Plate, caused by reduced plate interface slip during continental underthrusting, resulted in forearc closure (Malavieille and Trullenque 2009;Shyu et al 2011). Because of the oblique configuration of the Chinese continental margin and the Luzon Arc, the collision commenced in the north in Mio-Pliocene time and propagated southward (Suppe 1984), while northeastern Taiwan has entered post-collisional stage (Chen et al 2014) due to westward propagation of the Ryukyu subduction system with opposite polarity (Teng 1996;Wu et al 2009). The island is divided in two parts ( Fig.…”
Section: Geological Background and Samplingmentioning
confidence: 99%